Efektivitas Daun Jarak (Jatropha curcass Linn) Sebagai Anticacing Ascaridia galli dan Pengaruhnya terhadap Performa Ayam Lokal - S Suharti; K G Wiryawan; R Tiuria; Y Ridwan; S Fitriana; N Sumarni (Faculty of Animal Science, Bogor Agricultural University, 2010)
The present experiment was aimed to identify the phytochemical of Jatropha curcas leave extracted with water and methanol as an anthelmintic agent for Ascaridia galli, and its effect on native chicken performance. In vitro study of anthelmintic activity was conducted by counting the number of paralyzed worm dead-body of A. galli during 18 hours in petri dish containing different levels of extract, namely 0%, 1%, 2%, 3%, and 4% (w/v) and compared to the piperazine 0.5% (w/v). Eightteen birds of naturally A. galli-infected native chicken were used for the in vivo study. The treatments were 0%, 2%, 4%, 8%, and 16% of J. curcass leave extract, and 10% of piperazine using a completely randomized block design with 6 treatments and 3 replications. Parameters observed were fecal worm egg count, feed consumption, body weight gain, feed conversion ratio, and mortality. The results showed that water- and methanol-extracted J. curcas leave had similar composition of secondary metabolite compounds which is high in triterpenoid and steroid contents, respectively. Percentage of paralyzed A. galli was higher (P < 0.01) in water-extracted jatropha leaves. On the contrary, the dead-body percentage was higher (P < 0.05) in the methanol-extracted than that in the control group. In vivo study showed that leave meal significantly decreased (P < 0.05) fecal worm egg count. The leaf meal at the level 16% tended to increase feed consumption, body weight gain, and significantly decreased feed conversion ratio. In conclusion, J. curcas leave meal have anthelmintic activity to A. galli and could improve nutrient utilization of naturally A. galli-infected native chicken by decreasing feed conversion ratio.